Girl's Experiences of Child Marriage in Afghanistan: A Scoping Review - Shinwari, Zala; Herdiana, Ike (Journal of Educational, Health and Community Psychology, 2022)
This study aims to explore factors of child marriage and experiences of girls married below 18 in Afghanistan. A scoping review was conducted in accordance with the PRISMA-ScR procedure. Articles were searched from Science Direct, Scopus, Google Scholar and WoS databases. There were seven journal articles that were included based on the inclusion and exclusion criteria set. Meta-synthesis method was used in this research. We found many factors that exist in Afghanistan namely; poverty, illiteracy and luck of access to education, war and instability, cultural and traditional practices, ethnicity and geography and misinterpretation of religious texts are among the main ones. Consequently, girls suffer from many types of violence (physical, emotional and sexual, and other) and psychosocial problems. In spite of these facts there was no specific study in terms of psychological impacts, income level, cultural and religious background, and psychosocial impacts of child marriage based on the findings of this study.